Assessing the impact of the Russia-Ukraine war and COVID-19 on selected European currencies and key commodities - Aliu, Florin; Apanovych, Yelyzaveta; Bajra, Ujkan; Nuhiu, Artor (Journal of Business Economics and Management, 2024)
This study measures the spillover effects of the Russia-Ukraine war and the COVID-19 pandemic on currency pairs as the Russian ruble, Czech koruna, Polish zloty, Hungarian forint, Swedish krona, Bulgarian lev, Danish krone, Romanian leu, Ukrainian hryvnia, and Turkish Lira. By employing the TVP-VAR model we investigate the dynamic connectedness among these currencies and key energy and agricultural commodities. The data series encompasses two consecutive non-economic shocks – the Ukraine war and the COVID-19 pandemic – and a preceding period of general stability during 2018 and 2019. The importance of geopolitical context in shaping currency dynamics was present in countries with heavy dependence on Russian gas. The findings indicate a limited direct impact of commodity price fluctuations on the value of these currencies. At the same time, geopolitical decisions primarily related to the Russian Ruble and energy dependencies significantly impacted their valuation. The study reveals the complexity of currency dynamics and the influence of geopolitical risks and global health crises on exchange rate volatility and commodity dependencies.